GAMBARAN HASIL BELAJAR METODE DEMONSTRASI PRAKTIKUM IRIGASI KATETER PADA MAHASISWA S-1 ILMU KEPERAWATAN SEMESTER VI STIKES WIRA HUSADA YOGYAKARTA 2015 - Nur Yeti Syarifah (STIKES Wira Husada Yogyakarta, 2016)
ABSTRACT The Quality of education is closely related to the learning process. In the learning process raises the interaction between teachers and students. Through the interaction between teachers and students and interaction among students in the learning process will lead to positive impacts that can provide behavior change obtained learners after experiencing learning activities. The purpose of this study to determine student learning outcomes obtained after following the irrigated catheter with a practical demonstration of how they observed students using the guidelines for observation after mahaiswa following the learning process. The amount of samples in this research was 60 students that follows the course ofthe study from the beginning to the end of doing the research and willing to become respondents in the study. The instruments used in the form of guidelines for observation using a standard operating procedure that is standard. After the data collected then analyzed descriptive data and continued with a discussion based on a review of theory and research the authenticity of the line or not in line with the research. The results of this research by the characteristics of respondents aged 19-21 had the highest, amounting to 32 (53%) people, then the result of learning using practical demonstration of the highest in irrigated catheter with a value above 75 amounted to 42 students competent. The conclusion of this study is the description of learning outcomes in the practical demonstration of the methods of irrigation catheters with the number of respondents 60 students showed that 42 (70%) students have learning outcomes above 75 (competent).